PAPAN GYPSUM DARI SERBUK KAYU DAN SENYAWA BOR TERHADAP SIFAT MEKANIK DAN UJI BAKAR - Djoko Purwanto (Kementerian Perindustrian, 2013)
The using saw dust Lua, Kambang, Tarap wood and addition of boron solution on Modulus of Rupture (MOR), Modulus of Elasticity (MOE) and the fire resistant gypsum boar. The purpose of using saw dust wood and down the process of fire gypsum board. Treatment research that used of particle size (40 mesh and 60 mesh) saw dust wood, the percentage of sawdust and gypsum (300%, 400% and 500%), and the percentage of boron solution (1% and 2%). The results showed that the average value of Modulus of Rupture is between 16.68 to 31.11 kg/cm2; average Modulus of Elasticity is between 1129.80 to 3972.32 kg/cm2, and the average value of the fire resistant is between 20.32 to 46.88%. Value of the largest / best for Modulus of Rupture (31.11 kg/cm2), Modulus of Elasticity (3972.32 kg/cm2), and the burned area (20.32%) resulted tha tratment of sawdust particle size Kambang 40 mesh, the percentage wood sawdust and gypsum 500% and 2% boron solution. The increasing particle size saw dust, and the amount of concentration gypsum, then the value Modulus of Rupture and ), Modulus of Elasticity the greater, and percentage the fire resistant small.Keywords: gypsum board, wood sawdust, boron solution, mechanical strength, fire resistant.